1984
DOI: 10.1093/carcin/5.3.399
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous assessment of ethyl carbamate-induced SCEs in murine lymphocytes, bone marrow and alveolar macrophage cells

Abstract: At 3, 6, and 24 h after acute treatment of BD2F1 mice with 3.3 mmol/kg of ethyl carbamate, blood was drawn and cultured for SCE analysis. After blood sampling, the same mice were infused with BrdUrd for simultaneous assessment of SCEs in bone marrow and alveolar macrophage cells. In bone marrow and alveolar macrophage cells, maximum SCE responses (24.1 +/- 4.3; 24.2 +/- 3.8, respectively) were observed at 3 h post-exposure. Decreased SCE frequencies were observed at each later time. Relative to a single (3.3 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1987
1987
1998
1998

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The effect of 2-ME on baseline SCE frequency has been shown in mouse peripheral blood lymphocyte cultures where a 560 /zM concentration of the chemical doubled the baseline SCE frequency observed at lower doses (Goon and Conner, 1984). In addition, reducing agents such as 2-ME modulate mitogeninduced proliferation responses of both lymphoid cell lines and spleen cells (Broome and Jeng, 1973).…”
Section: Introductionmentioning
confidence: 98%
“…The effect of 2-ME on baseline SCE frequency has been shown in mouse peripheral blood lymphocyte cultures where a 560 /zM concentration of the chemical doubled the baseline SCE frequency observed at lower doses (Goon and Conner, 1984). In addition, reducing agents such as 2-ME modulate mitogeninduced proliferation responses of both lymphoid cell lines and spleen cells (Broome and Jeng, 1973).…”
Section: Introductionmentioning
confidence: 98%
“…Goon and Conner [1984] state that 2-ME is required to obtain successful growth of mouse IL PBLs, although MI data were not presented. However, Speit et al [1980] found that 10 pM 2-ME increased the frequency of CAs and 50 pM induced SCEs in V-79 cells.…”
Section: Resultsmentioning
confidence: 99%
“…In the few previous reports by other investigators culturing mouse IL PBLs for cytogenetic endpoints [Barren et al, 1982;Goon and Conner, 19841 2-ME is used as a growth supplement with some success. Goon and Conner [1984] state that 2-ME is required to obtain successful growth of mouse IL PBLs, although MI data were not presented. However, Speit et al [1980] found that 10 pM 2-ME increased the frequency of CAs and 50 pM induced SCEs in V-79 cells.…”
Section: Resultsmentioning
confidence: 99%
“…4 ppm. An increase in the percentage of first-division metaphases, as well as decreases in the percentages of second and third or higher division metaphases, were observed in the low dose exposure group.…”
Section: Resultsmentioning
confidence: 99%